Management of Students’ Smart Device use Behavior During Lectures at a University in Hanoi - Hung, Le Ngoc; Dung, Ha Kim; Chau, Doan Thi Dan; Anh, Nguyen Phuong; Hien, Vu Thi; Phuong, Bui Thi (VNU Journal of Science: Education Research; Vol 42 No 2DO - 10.25073/2588-1159/vnuer.5420, 2026)
In the context of digital transformation, the use of smart devices by university students for learning purposes has become increasingly prevalent, raising concerns regarding the effective management of students’ smart device use behavior during lectures. Drawing upon systems theory, behavioral theory, and smart school theory, this study investigates students’ smart device use behavior during lectures at a university in Hanoi. The findings indicate that, during classroom instruction, a majority of students spend a considerable amount of time using smart devices for various purposes. Consequently, such behavior requires both external management by lecturers and self-regulation by students in order to enhance teaching effectiveness and learning outcomes. Management measures implemented by universities, faculties, and lecturers should be diverse, flexible, and intelligently designed, incorporating both “authoritative” and “liberal” approaches while avoiding the conventional mindset of “if it cannot be controlled, it should be prohibited.” Furthermore, modern and smart educational management should aim to foster students’ trust and motivation in developing self-management and self-directed learning capacities, as reflected in their effective use of smart devices for R&D&B (research, development, and business) during classroom instruction at universities.